The Contribution of Arm Muscle Strength to the Under-Passing Ability of Youth Women's Athletes Volleyball - Fitriningsih; Agung Wahyudi (Universitas Negeri Semarang, 2026)
Volleyball is a sport that requires a lot of physical fitness, but judging by the Pervos Kendal Club, their training methods appear to be mediocre. Furthermore, players frequently make errors when passing, especially when facing fast serves. This issue is believed to be related to arm muscle stability, but there is limited research evaluating specific physical factors in young female athletes aged 10 to 15. The purpose of this study is to analyze the contribution of arm strength to the lower passing ability in KU Youth female athletes at the Kendal Pervos Club. The type of research conducted was a correlational descriptive research using a correlation test to find out how much of a relationship between variables, with a sample of 15 KU Youth female athletes at the Pervos Kendal Club. The study was conducted by taking data on the strength of athletes' arm muscles using Modified Push-ups and taking athletes' lower passing data using the Brumbach Forearms Pass Wall-Volley Test. The results showed that the average push-up ability was 20.93 and the average lower passing was 24.60. Hypothesis test through simple linear regression revealed a significant influence with a significance value of 0.002 (p< 0.05) and indigo tcount of 3.818. The results of the determination coefficient showed that the strength of the arm muscles contributed 52.9% to the ability to pass the bottom. It can be concluded that the results of this study show that arm muscle strength has a significant and strong relationship with the ability to pass under volleyball in female athletes of KU Belia Klub Pervos Kendal.